Use of Learning Media in Entrepreneurship Subjects Equality Education Paket C - Syuraini, Syuraini; Yolanda, Yolanda (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
Learning media used by tutors in the learning process at PKBM Farilla Ilmi are very suitable and attract the attention of the learning community. The results of this study found that the compatibility and attractiveness of the media in learning can increase the motivation of students to learn, so that students' understanding increases rapidly. Likewise the interaction between tutors and students and their peers is more increased because the media provided involves a lot of learning in the learning process. This study has a population of Paket C learners equivalent to high school, amounting to 60 people. While the sample is 30 people, which is half of the research target using classified random sampling techniques so that it is representative in representing each class. The results of this study are in accordance with the researchers' expectations expressed in the preliminary section about the success of the Paket C program in achieving high scores in Entrepreneurship subjects.